2013
DOI: 10.1111/jipb.12070
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Characterization of Ghd7.1, a Major Quantitative Trait Locus with Pleiotropic Effects on Spikelets per Panicle, Plant Height, and Heading Date in Rice (Oryza sativa L.)

Abstract: A quantitative trait locus (QTL) that affects heading date (HD) and the number of spikelets per panicle (SPP) was previously identified in a small region on chromosome 7 in rice (Oryza sativa L.). In order to further characterize the QTL region, near isogenic lines (NILs) were quickly obtained by self-crossing recombinant inbred line 189, which is heterozygous in the vicinity of the target region. The pleiotropic effects of QTL Ghd7.1 on plant height (PH), SPP, and HD, were validated using an NIL-F2 population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 61 publications
1
47
0
Order By: Relevance
“…In the Nipponbare/Kasalath cross, it delayed flowering under LDs and promoted flowering under SDs (Yano et al, 2000). In the Zhenshan97/Teqing and the Kita-ake/PA64S crosses, Hd2 delayed heading under LDs and had little effect under SDs (Liu et al, 2013; Yan et al, 2013; Gao et al, 2014). In our studies, photoperiod response of Hd2 disappeared when the functional allele Hd1 ZS97 showed no response to photoperiod in the background of ZS97, although the functional Hd1 ZS97 and Hd2 MY46 alleles continue to affect heading date by promoting and suppressing flowering, respectively, irrespective of the day-length conditions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the Nipponbare/Kasalath cross, it delayed flowering under LDs and promoted flowering under SDs (Yano et al, 2000). In the Zhenshan97/Teqing and the Kita-ake/PA64S crosses, Hd2 delayed heading under LDs and had little effect under SDs (Liu et al, 2013; Yan et al, 2013; Gao et al, 2014). In our studies, photoperiod response of Hd2 disappeared when the functional allele Hd1 ZS97 showed no response to photoperiod in the background of ZS97, although the functional Hd1 ZS97 and Hd2 MY46 alleles continue to affect heading date by promoting and suppressing flowering, respectively, irrespective of the day-length conditions.…”
Section: Discussionmentioning
confidence: 97%
“…In the last few years, an increasing number of genes/QTL for HD were reported to have pleiotropic effect on yield traits (Xue et al, 2008; Wei et al, 2010; Endo-Higashi and Izawa, 2011; Yan et al, 2011, 2013; Zhang et al, 2012; Liu et al, 2013; Zhao et al, 2013; Chen et al, 2014). However, most of them are involved in photoperiod response, contributing to yield enhancement accompanied with long growth duration under LDs (Xue et al, 2008; Wei et al, 2010; Endo-Higashi and Izawa, 2011; Yan et al, 2011, 2013; Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In rice, at least four genes involved in flowering regulation have been shown to have a pleiotropic role in regulating plant height and grain yield (Xue et al, 2008;Yan et al, 2011Yan et al, , 2013Gao et al, 2013;Liu et al, 2013b). Interestingly, all of these genes were commonly involved in flowering-regulated pathway of Ehd1-Hd3a.…”
Section: Identification Of Six Bncol Tfs With a Full-length Orfmentioning
confidence: 97%
“…Approximately 25 days were required for rice to complete panicle development from the growth phase transition to heading (Vergara et al, 1966; Chang et al, 1969; Liu et al, 2013). In Wuhan, the day length decreased from 13.5 h after August 6, thus the accessions that completed heading prior to August 30 initiated the transition from a vegetative to a reproductive phase under LD.…”
Section: Resultsmentioning
confidence: 99%